Prospective assessment of the prevalence of pelvic, paraaortic and high paraaortic lymph node metastasis in endometrial cancer - Kumar, Sanjeev (Gynecol Oncol, 2013)
OBJECTIVE: To prospectively define the prevalence of lymph node metastasis (LNM) in at risk endometrial cancer (EC). METHODS: From 2004-2008, frozen section based Mayo Criteria prospectively identified patients “not at-risk” of LNM (30% EC population; grade I/II, <50% myometrial invasion and tumor diameter ≤2cm) where lymphadenectomy was not recommended. The remaining 70% EC cohort was considered “at-risk” of LNM; where a systematic pelvic and infrarenal paraaortic lymphadenectomy was recommended. Patients were prospectively followed. The area between renal vein and inferior mesenteric artery (IMA) was labeled as high paraaortic area. For calculating the prevalence of LNM in high paraaortic area, the denominator was the population with known anatomic location of nodal tissue in relation to the IMA. RESULTS: Of the 742 patients, 514 were at risk; of which 89% underwent recommended lymphadenectomy. A mean (± standard deviation) of 36 (±14) pelvic and 18 (±9) paraaortic nodes were harvested. The prevalence of pelvic and paraaortic LNM was 17% and 12%, respectively. In presence of pelvic LNM, 51% had paraaortic LNM. In absence of pelvic LNM, 3% had paraaortic LNM; of which 67% were located exclusively in high paraaortic area. Among patients with paraaortic LNM, 88% had high paraaortic LNM; and 35% had only high paraaortic LNM. The cases of paraaortic LNM with negative pelvic nodes seemed to cluster in moderate to high grade endometrioid EC with ≥50% myometrial invasion. CONCLUSION: We present reference data for the prevalence of LNM in at-risk EC patients to guide lymphadenectomy decisions for clinical and research purposes.